AB0143 EXPRESSION OF HERV-E CLONE 4.1 GAG TRANSCRIPTS IN PERIPHERAL BLOOD MONONUCLEAR CELLS OF SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS. (2nd June 2020) - Talotta, R.; Troldborg, A.; Atzeni, F.; Laska, M. J.
Abstract : Background: Human endogenous retrovirus (HERV)-E clone 4.1 gag transcripts have been detected in peripheral blood mononuclear cells (PBMCs) of systemic lupus erythematosus (SLE) patients and seem to be associated to autoantibody production. To date, no study aimed to investigate whether their expression in cytokine-stimulated vs. unstimulated PBMCs of SLE patients could be related with clinical manifestations. Objectives: We aimed to correlate the expression of HERV-E clone 4.1 gag transcripts of unstimulated and phyto-haemoagglutinin (PHA) and interleukin-2 (IL-2)-stimulated PBMCs of SLE patients and healthy controls (HCs) and to evaluate the association between their expression and the demographic and clinical data of the SLE cohort. Methods: PBMCs were isolated from 18 SLE patients and 22 age- and gender-matched controls. Cells from 10 SLE patients and 15 HCs were harvested for RNA isolation, HERV-E clone 4.1 gag - and RPL-13-selective cDNA synthesis and SYBR Green RT-PCR analysis. The expression of gag transcripts was normalized to that of the housekeeping gene RPL-13, using the Pfaffl method. PBMCs of the remaining patients and HCs were stimulated with PHA/IL-2 and HERV- E clone 4.1 gag expression assessed as described before. Statistical analysis was carried using a SPSS software, version n.23. Results: Table 1 presents the demographic data of patients. The normalized mean ± SD gag expression was 1.6 ± 2.2 and 0.80 ± 0.79 in unstimulated PBMCs of SLE patients and HCs, respectively; and 1.1 ± 0.7 and 1.1 ± 0.4 in stimulated SLE and HC PBMCs, respectively. No significant difference emerged between patients and controls and between stimulated and unstimulated PBMCs (fig. 1 ). Gag transcripts expressed in PHA/IL-2-stimulated PBMCs of SLE patients significantly correlated with oronasal ulcers and high titers of anti- dsDNA antibodies (p=0.01 and p=0.004, respectively), while gag transcripts of unstimulated SLE PBMCs were significantly associated to the number of ACR criteria fulfilled (p=0.02). Conclusion: According to these preliminary findings, the expression of HERV-E clone 4.1 gag transcripts in unstimulated and stimulated PBMCs does not significantly differ between SLE patients and controls. The significant association with some clinical variables in SLE patients needs to be confirmed on wider cohorts. References: [1]Ogasawara H, et al. Quantitative analyses of messenger RNA of human endogenous retrovirus in patients with systemic lupus erythematosus. J Rheumatol. 2001;28(3):533-8. [2]Piotrowski PC, et al. Expression of human endogenous retrovirus clone 4-1 may correlate with blood plasma concentration of anti-U1 RNP and anti-Sm nuclear antibodies. Clin Rheumatol. 2005;24(6):620-4. Acknowledgments: None Disclosure of Interests: None declared